Perubahan Suhu, Ph Pulp dan Ph Keping Biji serta Aktivitas Polifenol Oksidase (PPO) pada Fermentasi Biji Kakao Mulia (theobroma Cocoa L.) - Sri Hartanti; Novi Sulistyani (agriTECH, 2003)
Studies were carried out on Kedaton Estate PTPN XII at Jember-East Java to indicate the changes of temperature of cocoa beans, pH of pulp, pH of cotyledon and polyphenol oxydase activity during fermentation process. The results showed that the temperature of heap beans rose from 25oC up to 40oC for 40 hours and reached 50oC after 60 hours of fermentation. The pH of pulp increased gradually from 4.07 to 5.07, but in contrast with the pH of cotyledon decreased from 6.69 to 4.55. While polyphenol oxydase decreased from 61.968 unit/mg protein to 4.220 unit/mg protein during 60 hours fermentation